Retracted: A clinical study of normothermic open heart surgery - Mir, Ishtiak Ahmed; Kumar, Ravinder; Digra, Madhu; Kumar, Dinesh (International Surgery Journal, 2017)
The following article from International Surgery Journal ‘A clinical study of normothermic open heart surgery’ (Int Surg J 2017;4:2429-33, doi: 10.18203/2349-2902.isj20173105), by Ishtiak Ahmed Mir, Ravinder Kumar, Madhu Digra, Dinesh Kumar was published in the Volume 4, Issue 8, August 2017, has been retracted upon authors request.